2007
DOI: 10.1111/j.1365-2818.2007.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized photodamage of the human erythrocyte membrane causes an invagination as a precursor of photohaemolysis

Abstract: SummaryFluorescence excitation can result in the formation of reactive oxygen species and free radicals damaging to live cells. In the case of erythrocytes, reaction of these reactive oxygen species with membrane components causes large-scale morphological changes followed by cell haemolysis. In an effort to understand the origin of these morphological changes, we have studied the consequences of localized photodamage on the erythrocyte membrane. For this, we irradiated a small area of the cell membrane using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Morphology is a common indicator of cell viability. Evaluating morphological changes during light exposure to assess possible cytotoxicity is a common practice used widely across various experimental studies 4 5 6 7 8 9 10 11 12 13 14 . When affected by light, cells often exhibit morphologies such as: necrosis, blebbing, formation of multiple nuclei or vacuoles, and swelling of mitochondria 3 9 .…”
mentioning
confidence: 99%
“…Morphology is a common indicator of cell viability. Evaluating morphological changes during light exposure to assess possible cytotoxicity is a common practice used widely across various experimental studies 4 5 6 7 8 9 10 11 12 13 14 . When affected by light, cells often exhibit morphologies such as: necrosis, blebbing, formation of multiple nuclei or vacuoles, and swelling of mitochondria 3 9 .…”
mentioning
confidence: 99%
“…We also investigated whether the SW technique caused any further photo-toxicity to the specimen compared to widefield epifluorescence imaging. It was observed that when using either imaging method, the red blood cell appeared to decay at a similar rate and in a manner that resembled the decay observed previously over 12 minutes under periodic focused laser illumination [ 62 ]. In the study of Wong et.…”
Section: Discussionmentioning
confidence: 73%
“…In the study of Wong et. al [ 62 ], it was found that membrane damage occurred even at low laser powers as the result of reactive oxygen species being generated via photo-hemolysis. This process has been hypothesized to be due to interactions between the reactive oxygen species and the membrane proteins, band 3 and spectrin [ 62 ], which has also been reported in studies using widefield illumination [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation